THE TERMS OF ADDRESS USED BY JAVANESE SANTRI (A CASE STUDY IN DARUL ‘ULUM ISLAMIC BOARDING SCHOOL, JOMBANG) - PUTRI, ANGGUN TYANARWATI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Terms of Address, Javanese Language, Darul ‘Ulum Islamic boarding school. Javanese language is one of various languages in Indonesia which is spoken by the people who lived in the province of Central Java, Yogyakarta and East Java. The Javanese language speech levels were divided into three Ngoko, Krama Madya, and Krama Inggil. There are some rules which are considered to be polite in Javanese communication, included the use of address terms. The writer conducts a research about address terms used by Javanese santri, case study in Darul ‘Ulum Islamic boarding school, Jombang by using Kridalaksana’s and Sadtono’s theory. This research focuses on two problems: (1) What Javanese terms of address are used by Javanese santri (2) What are the probable factors affecting the use of address terms.This research uses qualitative approach to describe the address terms phenomenon and answer the problems of study. The data of this research are transcription of direct interview and the daily conversation produced by male and female Javanese santri. Furthermore, the type of this research is case study because the writer considers in making the deep investigation about the use of address terms in Darul ‘Ulum Islamic boarding school.This research reveals that there are twenty two terms of address which are divided into four kinds; three terms in second personal pronouns categories such as sampeyan and panjenengan, seven terms in kinship categories such as bapak and ibu, eight terms in title and rank categories such as kyai and nyai and four terms in other categories such as santriwan and santriwati. In addition, the use of address terms influenced by several factors such as age, kin/ blood relationship, rank and title profession, and also social status.The writer hopes that this research can contribute a better and deeper understanding especially the address terms in Javanese society. She suggests for the next researchers who want to conduct a similar researchin sociolinguistics, especially the address terms phenomenon to use another theory to make their research more different and find the unique of address terms in different areas or cases.